CircZSWIM4 facilitates tumor development in lung adenocarcinoma by targeting miR-370-3p and miR-873-5p to regulate the axis of FOXM1/β-catenin: CircZSWIM4 facilitates tumor development in LUAD - Fan, Zhigang; Wang, Hongyan (Cellular and Molecular Biology, 2023)
Circular RNA (circRNA) is a kind of RNA generated by a covalently closed loop and possesses sophisticated capacities of gene regulation in tumorigenesis and development. However, the role of circZSWIM4 on lung adenocarcinoma (LUAD) remains largely unclear. In the present study, we used reverse transcription–qPCR (RT-qPCR) to examine whether circZSWIM4 was significantly overexpressed in LUAD cells. The impacts of circZSWIM4 on the properties of proliferation, apoptosis and migration were assessed by loss-of and gain-of-function assays, such as CCK-8 experiments, flow cytometry analysis and wound healing experiments. Moreover, TOP/FOP flash experiments and FISH experiments were carried out to prove that circZSWIM4 stimulated the Wnt/β-catenin pathway. Downstream targets of circZSWIM4 were forecasted by bioinformatics tools and validated by RNA immunoprecipitation (RIP), RNA pulls down as well as luciferase reporter experiments. Forkhead box M1 (FOXM1) was confirmed to be the corporate targets of miR-370-3p and miR-873-5p. Through co-IP assay, we verified the combination between FOXM1 and β-catenin. Totally, circZSWIM4 activated the Wnt/β-catenin pathway by targeting miR-370-3p and miR-873-5p to regulate FOXM1 and β-catenin and facilitated the progression of LUAD.